Ground response mechanism of entries and control methods induced by hard roof in longwall top coal caving panel. (February 2023) - Wang, Haosen; Wang, Jiong; Elmo, Davide; He, Manchao; Ma, Zimin; Gao, Chengzhang
Abstract: This paper presents an integrated approach for theoretical analysis and numerical modeling to investigate the ground response mechanism of entries and control methods induced by hard roof in longwall top coal caving panel (LTCC). The test site is located in the city of Jinzhong, Shanxi Province, China. A roof mechanical model for the main roof's different breaking positions was created to study the ground response mechanism of gob-side entries. The theoretical analysis indicated that the closer the main roof fracture line is to the gob, the smaller the lateral cantilever length of the main roof above the gob, and the surrounding rock of the roadway are more stable. Therefore, an innovative approach is proposed t to reduce the lateral cantilever length of the main roof above the gob area and automatically retain entry. This approach involves applying the "directional roof split blasting technique for pressure relief and automatic retained entry" (DRSBPRRE) in the thick coal seam of the LTCC panel. Meanwhile, numerical modeling results verified the results of the theoretical analysis. The results of the numerical simulation and practical application suggest that the DRSBPRRE approach can eliminate the cantilever length of the main roof, significantly reduce the peak vertical stress in the solid coal rib by approximately 13.76 % and reduce the surrounding rock damage and deformation. Therefore, the DRSBPRRE approach is a safe and efficient mining method for pressure relief and entry retention. This research could provide an important reference for thick coal seam LTCC panel non-pillar coal mining technology.